Penerapan Metode Lean Six Sigma untuk Mereduksi Waste pada Produksi Sepatu Sandal - Firna Elshadi; Chaznin R. Muhammad (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. UKM X is a company that produces sandals. In producing sandals, there are several problems including waste in the form of waiting time which causes waste in the form of inventory. And there are other wastes in the form of defects. Based on this phenomenon, the problems in this study are formulated as follows: (1) What types of waste are found in the sandal shoe production line? (2) What are the causes and how to overcome the waste that occurs? (3) What are the proposed improvements to overcome waste? This study uses the Lean Six Sigma metho. In the define stage, using tools in the form of a Value Stream Map, calculating Process Cycle Efficiency (PCE), and identifying waste based on the results of the seven waste questionnaire. The measure stage includes determining critical waste and calculating Defects Per Million Opportunity (DPMO). The analyze stage uses fishbone and makes Failure Mode and Effect Analysis (FMEA). Then the last stage is the improve and control stage using the Plan Do Check Act (PDCA) stage and projecting the proposed improvement using the Value Stream Map (Future State). The results of this study are: the operator of the raw material warehouse checks raw materials to be more thorough, selects the right supplier, prepares the raw material specification form and performs production scheduling by prioritizing products that have a shorter process to be produced first. Abstrak. UKM X merupakan perusahaan yang memproduksi sepatu sandal. Dalam memproduksi sepatu sandal terdapat beberapa persoalan meliputi waste berupa waiting time yang menyebabkan waste berupa inventory. Serta terdapat waste lain berupa defect. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Apa jenis waste yang terdapat pada lini produksi sepatu sandal? (2) Apa penyebab dan bagaimana cara mengatasi waste yang terjadi? (3) Apa usulan perbaikan untuk mengatasi waste? Penelitian ini menggunakan metode Lean Six Sigma. Pada tahap define menggunakan tools berupa Value Stream Map, perhitungan Process Cycle Efficiency (PCE), dan identifikasi waste berdasarkan hasil kuisioner seven waste. Tahap measure meliputi penentuan critical waste dan perhitungan Defects Per Million Opportunity (DPMO). Tahap analyze menggunakan fishbone dan pembuatan Failure Mode and Effect Analysis (FMEA). Kemudian tahap terakhir yakni tahap improve dan control menggunakan tahapan Plan Do Check Act (PDCA) dan memproyeksikan usulan perbaikan dengan Value Stream Map (Future State). Hasil dari penelitian ini adalah: operator bagian gudang bahan baku memeriksa bahan baku agar lebih teliti, pemilihan supplier yang tepat, menyiapkan form spesifikasi bahan baku dan melakukan penjadwalan produksi dengan memprioritaskan produk yang memiliki proses lebih pendek untuk diproduksi terlebih dahulu.